Beyond boolean, towards thinking : discovery systems and information literacy - Cmor, Dianne (2013)
Purpose – As discovery systems take the library world by storm, there is a new opportunity for user-centred information literacy programs to emerge. This paper aims to explore the impact that new web-scale discovery systems might have on information literacy programs and pedagogical approaches to library instruction.